Drama öğretmeninin yeterlilikleri - Ayşe OKVURAN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this study the efficiencies/skills which drama teachers should have were investigated. A drama teacher should have literature and drama history, theatre and arts education knowledge, manipulation of improvisation and, creating a positive atmosphere and, using materials skills and etc. Drama teachers, students, Ministry of Education and society’s coordination and communication and knowledge of drama and desire are necessary for improving teacher’s efficiencies